2009
DOI: 10.5005/jcdp-10-5-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Placement Techniques on the Microhardness of Class II (Slot) Resin Composite Restorations

Abstract: Aim:To analyze the influence of various placement techniques on Vickers microhardness of Class II cavities restored using resin composite in different depths and layers. Methods and Materials:Sixty-four standardized Class II cavities (5.0 × 3.0 × 1.5 mm 3 ) were prepared in sound human, maxillary premolars. The cavities were divided into four experimental groups (n=16) according to the composite placement technique used: incremental technique using a Palodent matrix (IP), incremental technique using a transpar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Therefore, the study concluded that the direction of layering should be adjusted in relation to the occlusion, and the way the force would be applied to the restoration [ 25 ]. Although the centripetal technique did not have a significant difference with the bulk technique in fracture resistance, there are still some advantages for this method, such as facilitation of a Class II buildup, establishment of a proper proximal contact, and provision of adequate light exposure for polymerization [ 26 ]. In this study, no significant difference was observed between the fracture resistances of specimens restored with Filtek P60 or Nulite F. According to the higher percent of volumetric filler content in Nulite F (71%) than Filtek P60 (61%), a superior fracture resistance was expected for Nulite F. The fracture toughness of BIS-GMA resin short-glass fiber composites with filler contents of 40, 50, 60, and 70% was measured in a study, and the results showed that the compressive strength was dependent on the percent of filler content, and the highest fracture resistance was obtained at the 50% filler content [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the study concluded that the direction of layering should be adjusted in relation to the occlusion, and the way the force would be applied to the restoration [ 25 ]. Although the centripetal technique did not have a significant difference with the bulk technique in fracture resistance, there are still some advantages for this method, such as facilitation of a Class II buildup, establishment of a proper proximal contact, and provision of adequate light exposure for polymerization [ 26 ]. In this study, no significant difference was observed between the fracture resistances of specimens restored with Filtek P60 or Nulite F. According to the higher percent of volumetric filler content in Nulite F (71%) than Filtek P60 (61%), a superior fracture resistance was expected for Nulite F. The fracture toughness of BIS-GMA resin short-glass fiber composites with filler contents of 40, 50, 60, and 70% was measured in a study, and the results showed that the compressive strength was dependent on the percent of filler content, and the highest fracture resistance was obtained at the 50% filler content [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of low-viscosity materials to adapt to dentinal irregularities allows them to create an intimate bond with microstructural cavity defects prior to the placement of the paste-like restorative composite [84]. In our study, the centripetal method as the cavity-filling method was chosen, because studies have shown that fillings obtained in this way have the highest degree of microhardness [85].…”
Section: Discussionmentioning
confidence: 99%